The Enlightenment Ideas in the Bulgarian 19th Century. The Kardzhalian Topic in the Works of Vera Mutafchieva - Алипиева, Антоанета (Poznańskie Studia Slawistyczne, 2018)
The article examines the Enlightenment ideas in the part of Vera Mutafchieva’s work. The time of Kardzhali, a specific period of chaos and marauding in the Ottoman Empire in the 18th and 19th century, is a period of the formation of enlightenment processes that Mutafchieva depicted through images and themes in her novels and scientific studies. The author is an Ottoman specialist known worldwide and one of the greatest novelists in Bulgaria. In her novels, she portrays philosophical and geopolitical ones that characterize the historical epoch embodied in her works.